2014
DOI: 10.1002/ptr.5188
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Botanical Characteristics, Phytochemistry, and Pharmacology of Astragalus membranaceus (Huangqi)

Abstract: Astragalus membranaceus is one of the most widely used traditional Chinese herbal medicines. It is used as immune stimulant, tonic, antioxidant, hepatoprotectant, diuretic, antidiabetic, anticancer, and expectorant. The current paper reviews the botanical characteristics, phytochemistry, and pharmacology of Astragali Radix. Information on Astragali Radix was gathered via the Internet (using Google Scholar, Baidu Scholar, Elsevier, ACS, Medline Plus, CNKI, and Web of Science) as well as from libraries and local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
376
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(381 citation statements)
references
References 43 publications
1
376
0
4
Order By: Relevance
“…Flavonoids are also important constituents of Astragali radix, a traditional Chinese herbal medicine used to treat a wide variety of disease states for its anti-inflammatory and other properties (Fu et al, 2014). Ruan et al (2015) in this issue examine the extent to which the rat gut microbiota alter glucuronidation and some pharmacologic properties of the most abundant flavonoid present in Astragali radix, calycosin-7-O-b-D-glucoside.…”
Section: Impact Of the Microbiota On The Metabolism And Bioavailabilimentioning
confidence: 99%
“…Flavonoids are also important constituents of Astragali radix, a traditional Chinese herbal medicine used to treat a wide variety of disease states for its anti-inflammatory and other properties (Fu et al, 2014). Ruan et al (2015) in this issue examine the extent to which the rat gut microbiota alter glucuronidation and some pharmacologic properties of the most abundant flavonoid present in Astragali radix, calycosin-7-O-b-D-glucoside.…”
Section: Impact Of the Microbiota On The Metabolism And Bioavailabilimentioning
confidence: 99%
“…Studies have shown that astragaloside IV and campanulin are active compounds with good pharmacological effects and they are indicators in Chinese Pharmacopoeia (Zhang et al 2011). Therefore, the contents of astragaloside IV, campanulin, calycosin, kaempferol, formononetin, ononin, quercetin, and APS were determined for the quality evaluation of a. mongholicus, and the methodology has been established by our team in a previous study (Fu et al 2014). The contents of chemical constituents in a. mongholicus are listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…a. mongholicus is a herb with multiple geographic origins. The provinces of Gansu, Shanxi, and Inner Mongolia are the major producing areas in China, of which Inner Mongolia and Shanxi are traditionally regarded as top-geoherb regions (Fu et al 2014). However, quality variations have existed in different herb-producing areas (Yao et al 2012), and the rapid, effective, and non-destructive In general, the aroma of a. mongholicus is an important index to evaluate its quality (Qi et al 2006;Zheng et al 2015).…”
mentioning
confidence: 99%
“…mongholicus (Bge.) Hsiao [1], is popular in clinical practice for treating hypertension, heart disease, diabetic nephropathy, viral hepatitis, and other diseases [2]. Conventionally, RA is regarded as a sweet, warm-natured drug, without any distinct toxicity and side effects in regular dosages [3].…”
Section: Introductionmentioning
confidence: 99%